AMPARO PROCEEDING: CRITERIA DEVELOPED BY THE CONSTITUTIONAL CHAMBER TO DEFINE ITS JURISDICTION VIS-À-VIS ORDINARY COURTS AND THEIR IMPLICATIONS FOR LEGAL CERTAINTY AND ENVIRONMENTAL AND CLIMATE JUSTICE - Peña Chacón, Mario (2025)
This article examines the evolving jurisprudence of Costa Rica’s Constitutional Chamber in environmental matters, highlighting its shift from a broadly inclusive approach—grounded in the pro actione principle—towards increasingly restrictive criteria regarding jurisdiction over environmental amparo proceedings.